Intelligent Information Dissemination Scheme for Urban Vehicular Ad Hoc Networks. (5th March 2015) - Yang, Jinsheng; Liu, Changqing; Wu, Shih-Lin
Abstract : In vehicular ad hoc networks (VANETs), a hotspot, such as a parking lot, is an information source and will receive inquiries from many vehicles for seeking any possible free parking space. According to the routing protocols in literature, each of the vehicles needs to flood its route discovery (RD) packets to discover a route to the hotspot before sending inquiring packets to the parking lot. As a result, the VANET nearby an urban area or city center may incur the problem of broadcast storm due to so many flooding RD packets during rush hours. To avoid the broadcast storm problem, this paper presents a hotspot-enabled routing-tree based data forwarding method, called the intelligent information dissemination scheme (IID). Our method can let the hotspot automatically decide when to build the routing-tree for proactive information transmissions under the condition that the number of vehicle routing discoveries during a given period exceeds a certain threshold which is calculated through our developed analytical packet delivery model. The routing information will be dynamically maintained by vehicles located at each intersection near the hotspot if the maintaining cost is less than that of allowing vehicles to discover routes themselves. Simulation results show that this method can minimize routing delays for vehicles with lower packets delivery overheads.